STRUKTUR SESAR DI PULAU JAWA BAGIAN BARAT BERDASARKAN HASIL INTERPRETASI GEOLOGI - -, Iyan Haryanto (Fakultas Teknik Geologi Universitas Padjadjaran, 2013)
There are four major fault lines pattern that developed in Tertiary sedimentary rocks in the Western Part of Java Island, that are the east-west, north-south, northwest-southeast and northeast-southwest. Fault structures with the east-west direction generally existed as a reverse fault and as the main fault patterns that control the distribution of rocks on the surface. Regionally, together with structural folds, these fault structures has formed the thrust fold belt structure. The other faults direction, generally known as the secondary faults that formed simultaneously with the thrust fold belt structure. These faulst are generally as strike slip fault or oblique faults that are transtensional or transpressional. This fault pattern is formed when a horizontal force strength differences in each segment. From the Compilation of the fold structures data, faults and the stratigraphy, it can be concluded that the geological structure developed in Tertiary sedimentary rocks in the western part of Java Island, began formed at late Tertiary, under the main compressional system, which is north-south trending.